Strategic solutions of business innovation-driven growth mainstreaming - Smolinska, N. V. (Національний університет "Львівська політехніка", 2013)
The method of development of the business innovation capacity and corporate culture level evaluation, that allows identification of this level growth or deterioration within the specific period of time, is the key problem of the article. The data received permit to work out the matrix “the level of corporate culture vs. the level of innovation capacity” of the business in order to reveal the business’ position in this matrix and select the innovation-driven growth strategy of this business.
Keywords: development; innovation capacity; corporate culture level evaluation; management solutions